2014
DOI: 10.1111/jsap.12248
|View full text |Cite
|
Sign up to set email alerts
|

Extended proximal trochleoplasty for the correction of bidirectional patellar luxation in seven Pomeranian dogs

Abstract: Seven Pomeranians with bidirectional patellar luxation (BPL) were prospectively studied regarding aetiology and results of a new surgical technique. Radiographic evaluation of the ratio between patellar ligament length and patellar bone length revealed no differences between Pomeranians with bidirectional patellar luxation and healthy stifle joints. Functional rather than anatomic patella alta might be associated with bidirectional patellar luxation in Pomeranians. The surgical outcome of extended proximal tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
33
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 10 publications
2
33
1
1
Order By: Relevance
“…This study shows that K‐wedge recession trochleoplasty significantly increased the coverage of the proximal trochlear by the patella, which was maintained at 12 months postoperative without lameness. Minimal progression of osteophyte presence was identified 12 months postoperative, as reported previously . The K‐wedge recession trochleoplasty offers an alternate to modified wedge recession with proximal excisional trochleoplasty in dogs with MPL.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…This study shows that K‐wedge recession trochleoplasty significantly increased the coverage of the proximal trochlear by the patella, which was maintained at 12 months postoperative without lameness. Minimal progression of osteophyte presence was identified 12 months postoperative, as reported previously . The K‐wedge recession trochleoplasty offers an alternate to modified wedge recession with proximal excisional trochleoplasty in dogs with MPL.…”
Section: Discussionsupporting
confidence: 69%
“…The proximal end of the K‐wedge is in the cortical bone of the distal femur, which is 2–3 mm proximal from the patella position with the stifle extended. Wangdee et al reported that the periosteum should be continuous with the wedge to allow for blood supply. Wangdee et al also recommended that the exposed cancellous and cortical bone of the distal femur should be covered to reduce enthesophyte formation at the proximal patella and osteophyte formation in the extended trochlea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A proximal position of the patella in the trochlear groove in stance may coincide with bidirectional patellar luxation in Pomeranians, even though the L:P ratio is normal (13). This might be because functional patella alta is a result of hyperextension of the stifle joint during locomotion rather than a long patellar ligament (16).…”
Section: Discussionmentioning
confidence: 99%